Optimal Income Taxation with Endogenous Human Capital - Bas Jacobs (Tinbergen Institute, 2002)
This paper augments the theory of optimal linear income taxation by taking into account human capital accumulation as a dimension of labor supply. The distribution of earning potentials is endogenous because agents differ in the ability to learn. Taxation affects utilization rates of human capital through labor supply responses. The costs of education that are not deductible from the income tax distort the learning decision as well. We show theoretically that the trade-off between efficiency and equity is worsened. Quantitative analysis shows that the distortionary costs of taxation increase substantially when human capital formation is endogenous.
Keywords: H21; J22; J24; 330; optimal linear taxation; labor supply; human capital accumulation; Einkommensteuer; Optimale Besteuerung; Bildungsinvestition; Arbeitsangebot; Theorie